2014
DOI: 10.3748/wjg.v20.i43.16318
|View full text |Cite
|
Sign up to set email alerts
|

Two-week treatment with proton pump inhibitor is sufficient for healing post endoscopic submucosal dissection ulcers

Abstract: Two-wk treatment with a proton pump inhibitor is as effective as four-week treatment for healing post ESD ulcers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 26 publications
1
16
0
Order By: Relevance
“…Previously, we reported the efficacy and safety of esomeprazole for post‐ESD ulcers of the stomach in a randomized controlled trial (RCT) (UMIN000006951) . Patients in the current study prospectively underwent gastric ESD, were given vonoprazan and, at 4 weeks after ESD, ulcer size was measured for our clinical trial (UMIN000018169).…”
Section: Methodsmentioning
confidence: 99%
“…Previously, we reported the efficacy and safety of esomeprazole for post‐ESD ulcers of the stomach in a randomized controlled trial (RCT) (UMIN000006951) . Patients in the current study prospectively underwent gastric ESD, were given vonoprazan and, at 4 weeks after ESD, ulcer size was measured for our clinical trial (UMIN000018169).…”
Section: Methodsmentioning
confidence: 99%
“…Arai et al . 18 ) reported that 2 weeks of PPI administration may be sufficient for ulcer healing. However, there is no consensus regarding the proper duration of PPI administration after ESD.…”
Section: Discussionmentioning
confidence: 99%
“…Arai et al . 18 ) compared the staging of post-ESD ulcers at week in patients receiving esomeprazole plus rebamipide for 2 weeks and 4 weeks, and found that the number of patients with ulcers in the healing/scar stage was 20/6 and 28/5, respectively. In these studies, patients received intravenous administration of 20 mg omeprazole for one or two days after the procedure.…”
Section: Discussionmentioning
confidence: 99%
“…Arai et al [22] revealed that 2 weeks of PPI treatment had effects similar to those of 4 weeks of PPI treatment with regard to post-ESD ulcer healing. Takayama et al [23] revealed that 1 week of PPI treatment followed by 7 weeks of rebamipide treatment had effects similar to those of 8 weeks of PPI treatment with regard to post-ESD ulcer healing.…”
Section: Complications and Their Preventionmentioning
confidence: 99%
“…Five RCTs regarding post-ESD ulcer healing were identified [22][23][24][25][26]. Arai et al [22] revealed that 2 weeks of PPI treatment had effects similar to those of 4 weeks of PPI treatment with regard to post-ESD ulcer healing.…”
Section: Complications and Their Preventionmentioning
confidence: 99%